2005
DOI: 10.1590/s1415-54192005000500010
|View full text |Cite
|
Sign up to set email alerts
|

Determinação das medidas dentárias mésio-distais em indivíduos brasileiros leucodermas com oclusão normal

Abstract: Em 60 modelos de gesso ortodônticos foram medidas as larguras mésio-distais dos dentes, de segundo molar a segundo molar, em ambos os arcos, utilizando um paquímetro digital modificado. Este trabalho teve como objetivos determinar o valor médio para a largura de cada dente e observar a presença de dimorfismo sexual, em indivíduos brasileiros leucodermas, com a média de idade de 16,03 anos (25 do gênero masculino e 35 do gênero feminino), não tratados ortodonticamente e portadores de oclusão normal, apresentand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
(17 reference statements)
2
7
0
2
Order By: Relevance
“…Therefore, in absolute terms it is suggested that men and women be studied separately. These results agree with most authors, 10,14,19,20,22 with the sole exception of Baum and Cohen, 3 who, in attempting to assess the occurrence of dimorphism, found striking similarities between patients of both genders.…”
Section: Outcome Analysis Sexual Dimorphism Between Genderssupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, in absolute terms it is suggested that men and women be studied separately. These results agree with most authors, 10,14,19,20,22 with the sole exception of Baum and Cohen, 3 who, in attempting to assess the occurrence of dimorphism, found striking similarities between patients of both genders.…”
Section: Outcome Analysis Sexual Dimorphism Between Genderssupporting
confidence: 92%
“…To this end one sees studies focused on several areas, such as dentistry, 15 endodontics, 9 orthodontics, 1,5,12,17,18,22 prosthesis 16 and forensics. 6,21 As the first author to publish a table of measurements of human teeth, Black 4 is credited as having conducted the first and most detailed study of dental morphology and anatomical nomenclature of all times.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental occlusion is a complex formed by the mandible, maxilla, TMJ, and the elevator and depressor muscles of the jaw (13) . Normal occlusion is characterized by the harmony of this complex (14) , and maintaining occlusal balance is essential to the proper functioning of the masticatory system (15) . Malocclusion is defined as an abnormal relationship between the teeth and the dental arch, which assume an undesirable contact with the elements of the opposite arch (13) .…”
Section: Introductionmentioning
confidence: 99%
“…A normal occlusion is characterized by a complex harmony and a normal position of dental inclined planes, which in accordance with their bone bases and muscle forces, exhibit contact points and correct axial inclinations 5 .…”
Section: Introductionmentioning
confidence: 99%